2021
DOI: 10.3389/fresc.2021.788087
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal Cortex and Supplementary Motor Area Activation During Robot-Assisted Weight-Supported Over-Ground Walking in Young Neurological Patients: A Pilot fNIRS Study

Abstract: Introduction: Rehabilitation therapy devices are designed for practicing intensively task-specific exercises inducing long-term neuroplastic changes underlying improved functional outcome. The Andago enables over-ground walking with bodyweight support requiring relatively high cognitive demands. In this study, we investigated whether we could identify children and adolescents with neurological gait impairments who show increased hemodynamic responses of the supplementary motor area (SMA) or prefrontal cortex (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Hypothesis 1 changes in activation patterns hypothesis: Drawing from neuroimaging studies, it is hypothesized that during the early stages of motor learning, there will be a significant increase in activation in PFC and SMA. This is aligned with the finding, where early stages of motor skill acquisition were associated with increased activity in these regions (van Hedel et al., 2021). Conversely, in the later stages of learning, we anticipate a significant increase in activation in M1 and PL, as demonstrated by the posterior shift in cortical activation observed in studies (Krüger et al., 2020; Sun et al., 2022).…”
Section: Introductionsupporting
confidence: 90%
“…Hypothesis 1 changes in activation patterns hypothesis: Drawing from neuroimaging studies, it is hypothesized that during the early stages of motor learning, there will be a significant increase in activation in PFC and SMA. This is aligned with the finding, where early stages of motor skill acquisition were associated with increased activity in these regions (van Hedel et al., 2021). Conversely, in the later stages of learning, we anticipate a significant increase in activation in M1 and PL, as demonstrated by the posterior shift in cortical activation observed in studies (Krüger et al., 2020; Sun et al., 2022).…”
Section: Introductionsupporting
confidence: 90%
“…Hubertus J.A. Van Hedel et al [ 40 , 45 ] reported the effects of gait training using a robotic device in young neurological patients with CP as well as CIP, hemiparesis, and demyelination. In addition, robot-assisted gait therapy is increasingly being used in pediatric neurorehabilitation for neurological gait disorders, including meningomyelocele (spina bifida) as well as CP, complementing conventional physical therapy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Holper and colleagues ( 67 ) analyzed changes in the activation of the primary motor cortex (M1) using functional near-infrared spectroscopy (fNIRS) in healthy adults performing hand exercises of different complexity. We recently investigated whether the prefrontal cortex and the supplementary motor area showed increased activations when children with gait impairments walked in the over-ground bodyweight supporting device Andago compared to treadmill walking ( 68 ). Walking in the Andago appears closer to reality and requires more concentration than walking on a treadmill ( 69 ).…”
Section: Quantifying and Measuring Intensitymentioning
confidence: 99%
“…Both studies indicate that the more complex tasks resulted in increased levels of brain activation. However, fNIRS currently seems too complicated to apply clinically ( 68 ).…”
Section: Quantifying and Measuring Intensitymentioning
confidence: 99%